2021
DOI: 10.1039/d1cp00065a
|View full text |Cite
|
Sign up to set email alerts
|

Electron-induced fragmentation mechanisms in organic monomers and their implications for photoresist optimization for EUV lithography

Abstract: Secondary electrons generated during the Extreme Ultraviolet Lithography (EUVL) process are predominantly responsible for inducing important patterning chemistry in the photoresist film. Therefore, it is crucial to understand the electron-induced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These include thin film synthesis via electron-enhanced atomic layer deposition (EE-ALD) [ 14 , 15 , 16 , 17 ] and chemical vapor deposition (CVD) [ 18 , 19 ]; direct write 3D nanoprinting by gas assisted focused electron beam induced deposition (FEBID) [ 20 , 21 , 22 , 23 ]; and electron lithography with inorganic/metal organic resist materials [ 24 , 25 , 26 , 27 ], organic resists [ 28 ], ice lithography [ 29 , 30 ], and cryo-lithography with metal containing resists [ 31 ]. Furthermore, electron-induced reactions also play a vital role in extreme ultraviolet lithography [ 32 ] where the high-energy photons induce secondary electrons in metal-organic resists. The same holds for 3D nanoprinting by gas-assisted focused-ion-beam-induced deposition (FIBID) [ 33 ], wherein they determine the shape and composition of deposits, especially for noble gas FIBID performed in modern helium and neon ion microscopes [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include thin film synthesis via electron-enhanced atomic layer deposition (EE-ALD) [ 14 , 15 , 16 , 17 ] and chemical vapor deposition (CVD) [ 18 , 19 ]; direct write 3D nanoprinting by gas assisted focused electron beam induced deposition (FEBID) [ 20 , 21 , 22 , 23 ]; and electron lithography with inorganic/metal organic resist materials [ 24 , 25 , 26 , 27 ], organic resists [ 28 ], ice lithography [ 29 , 30 ], and cryo-lithography with metal containing resists [ 31 ]. Furthermore, electron-induced reactions also play a vital role in extreme ultraviolet lithography [ 32 ] where the high-energy photons induce secondary electrons in metal-organic resists. The same holds for 3D nanoprinting by gas-assisted focused-ion-beam-induced deposition (FIBID) [ 33 ], wherein they determine the shape and composition of deposits, especially for noble gas FIBID performed in modern helium and neon ion microscopes [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A −20 V bias was applied to the samples during the measurement in order to enhance the photoemission signal: it should be noted that such accelerating electric field forms between the surface of the film and the electron detector and not within the photoresist film itself, thus not affecting the electronic processes in the cascade during the exposure to EUV light. Because copolymer, PAG, and quencher molecules are sensitive to damage from ultraviolet and shorter wavelength radiations, 11 care was taken to minimize the exposure of the samples by using a one-point-perexposure acquisition strategy: the beam position on the sample was shifted by moving the stage by 0.5 mm at the beginning of each measurement. This procedure ensured that each spectrum was taken on fresh location of the photoresist.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…As a result, only a minority of chemical changes in the photoresist are driven by direct photoabsorption and radiolysis . On the contrary, photoabsorption of EUV light promotes few primary electrons (mostly from the valence band) into high kinetic-energy (≈80 eV) photoelectrons, which, in turn, generate a much larger cascade of secondary electrons via electronic energy loss events. , Recent studies have reported that the cascade is made of mostly low kinetic-energy (<8 eV) electrons, which are very efficient and selective , at deprotecting organic and metal-oxide molecules that make up EUV photoresists, owing to resonant mechanisms such as dissociative electron attachment and dissociative ionization . As a result, low-energy electrons are chiefly responsible for the lithographic exposure mechanism that triggers polymer deprotection and solubility switch in conventional chemically amplified photoresists (CAR), ligand scission and condensation in metal-oxide-condensed photoresists, and main-chain scission in organic (co)­polymers .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Gas phase photoelectron spectroscopy and photoionization mass spectrometry yield information on the initial photoionization step, [3][4][5] whereas the chemistry induced by secondary low energy electrons can be investigated using focused electron beams to study dissociative electron impact ionization and dissociative electron attachment in the gas phase. 6 The deep insights gained in such experiments can then be used to understand experiments on thin films, such as photoemission, which also adds information on the kinetic energy distribution of secondary electrons, [7][8][9] or outgassing experiments. The latter can identify charged and neutral fragment species that leave the surface of the thin film during EUV exposure.…”
Section: Introductionmentioning
confidence: 99%